The resurrection of Jesus apologetics, criticism, history - Allison, Dale C. 1955- (London Bloomsbury Publishing Plc, 2021)
Intro -- Title Page -- Dedication -- Contents -- Foreword -- Part I. Setting the Stage -- 1. Overture -- 2. Options -- Part II. Historical-Critical Studies -- 3. Formulae and Confessions -- 4. Appearances and Christophanies -- 5. The Story of the Tomb: Friday -- 6. The Story of the Tomb: Sunday -- 7. Resurrected Holy Ones? -- 8. Rudolf Pesch Redivivus? -- Part III. Thinking with Parallels -- 9. Apparitions: Characteristics and Correlations -- 10. Visions: Protests and Proposals -- 11. Enduring Bonds -- 12. Rainbow Body -- 13. Cessationism and Seeing Jesus -- 14. Zeitoun and Seeing Mary -- Part IV. Analysis and Reflections -- 15. Some Tenuous Arguments: Apologetical -- 16. Some Tenuous Arguments: Skeptical -- 17. Inferences and Competing Stories -- 18. Overreach and Modest Results -- Coda -- Index of References -- Index of Authors -- Index of Subjects -- Copyright.
Description based on publisher supplied metadata and other sources
Keywords: Resurrection of Jesus Christ-Biblical teaching; Electronic books